PENGARUH FINANCIAL KNOWLEDGE TERHADAP FINANCIAL BEHAVIOR DENGAN FINANCIAL ATTITUDE SEBAGAI VARIABEL INTERVENING - Tia Apriani; Mardiyati Mardiyati; Megawati Megawati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
The positive impact of technological advances is to make it easier for humans to meet their needs, and the negative impact is that it will make humans spend their resources to meet their desires and not their needs. So, if the fulfillment of these needs is not well controlled, it will have an impact on the future and financial behavior of humans. One of the variables that influence financial behavior is financial knowledge. The implementation of good financial behavior is not an easy thing for students to do. This study examined the financial behavior of students of IBE Indonesia in the 5th and 7th semesters of the accounting department. Thus, the students should have good financial knowledge in managing their finances, so that financial problems can be avoided. The population in this study was 144 students and the sample was 64 students. the sample was determined using the formula of Taro Yamane. The results of this study were the effect of directly stating that the variable financial knowledge has a significant influence (p < 0.001) on the variable financial behavior with an effect of 0.068. Effect indirectly stated that the variable financial knowledge mediated by the variable financial attitude has a significant effect (p < 0.05) on the variable Financial Behavior with an effect of 0.018. The total effect stated that the variable financial knowledge mediated by the variable financial attitude has a significant effect (p < 0.001) on the variable Financial Behavior with an effect of 0.087. Keywords: Financial Knowledge, Financial Behavior dan Financial Attitude